Ichthyosiform sarcoidosis: report of three cases from Japan and literature review - Miura, Takako; Kato, Yasunobu; Yamamoto, Toshiyuki (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Cutaneous lesions of sarcoidosis present with various manifestations including specific and non-specific cutaneous lesions. Ichthyosiform sarcoidosis is a rare form of cutaneous sarcoidosis, presenting with asymptomatic, adherent, polygonal scales, mainly appearing on the lower limbs. Ichthyosiform sarcoidosis has a predilection for dark-skinned races, and cases affecting Japanese patients have rarely been reported in English literature. We herein describe three Japanese cases of ichthyosiform sarcoidosis on the lower limbs. All of the patients were female, with an age range of 57-69 years old. Histologically, sarcoidal granulomas were located in the mid- to lower dermis. All cases had scar sarcoidosis on the knees. Furthermore, Case 1 presented with papular sarcoidosis on the back, and Case 3 presented with subcutaneous nodules on the buttock as well as erythema nodosum-like lesions on the lower legs. All patients had lung sarcoidosis, but ocular sarcoidosis was seen in only Case 2. Case 3 showed Heerfordt syndrome with facial nerve paralysis. Histological features showed that the granular layers were scarcely detected in the overlying epidermis; however, filaggrin expression was not decreased. Sarcoidal granulomas accumulated around the sweat glands in one case, whereas those features were not detected in the other two cases. In conclusion, ichthyosiform cutaneous sarcoidosis may be overlooked or misdiagnosed as xerotic dry skin which is frequently found in elderly people, and ichthyosiform cutaneous lesions may be more prevalent than previously estimated.